Impella RP for treatment of right ventricular shock: Appropriate unloading never gets old. Issue 2 (14th August 2020) - Goldstein, James A.; Hanson, Ivan
Key Points: Rapid restoration of hemodynamics is key to successful shock management. The failing right ventricular (RV) is resilient and recovers if hemodynamics are supported while the underlying insulting cause is alleviated. Inotropic/vasopressor drugs constitute a "double‐edged sword" that augment hemodynamics, but exacerbate myocardial and multiorgan injury. Impella RP mechanical support for RV shock stabilizes hemodynamics and is associated with favorable clinical outcomes.